The struggle between the State and the drunkard - Daly, E.D. (Statistical and Social Inquiry Society of Ireland, 1897)
No one can be competent to discuss the Drink Question unless he has thought over it sufficiently to realize how complicated the subject necessarily is. It is intimately interwoven with details of economic laws which pursue their course regardless of preacher and moralist; and under which causes generated by want of work, vile housing, and widely spread ignorance move on to degradation and drunkenness as their effects. Even beneath such a reign of law, however, human character may struggle and be helped upwards by the influence and example of friends, neighbours, and teachers of all kinds; while State interference through Parliament can do much to repress the forces of evil and secure at least fair play for the weak and the struggling. Thus the great cause of national sobriety is open to and requires many different lines of social inquiry and action, and no paper such as this could possibly deal with all of them.
Read Tuesday, 23rd February, 1897
Keywords: Drunkenness, Policy issues; Alcoholism, Policy issues; 314.15